1993
DOI: 10.1111/j.1439-037x.1993.tb01057.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Component Densities on the Productivity of Soybean/Maize and Soybean/Sorghum Intercrop

Abstract: Field experiments were conducted during the wet seasons of 1986 and 1987 at the Yandev Agricultural Experiment Station to investigate the effects of component density on the yield of sorghum or maize intercropped with soybean. Seed yield of the monocrops of sorghum, maize and soybean were higher than the individual components in the intercrops. Yields of component crops in the intercrop varied significantly with the components population density. The sorghum/soybean intercrops which had LER (Land Equivalent Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
14
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
6
14
1
Order By: Relevance
“…Varieties IT89KD-391, IT90K-277-2 and IT90K-372-1-2 recorded higher head weight of 1750kg/ha, 1740kg/ha and 1880kg/ha respectively. This result agrees with the findings of Pal et al, (1993) who reported yield advantages of legume-cereal intercropping over sole cropping. In 1998, highest head weight was recorded for sorghum when intercropped with varieties IT90K-277-2 (1791kg/ha) and IT90K-372-1-2 (1750kg/ha) when compared to sole sorghum head weight (1625kg/ha) ( Table 6).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Varieties IT89KD-391, IT90K-277-2 and IT90K-372-1-2 recorded higher head weight of 1750kg/ha, 1740kg/ha and 1880kg/ha respectively. This result agrees with the findings of Pal et al, (1993) who reported yield advantages of legume-cereal intercropping over sole cropping. In 1998, highest head weight was recorded for sorghum when intercropped with varieties IT90K-277-2 (1791kg/ha) and IT90K-372-1-2 (1750kg/ha) when compared to sole sorghum head weight (1625kg/ha) ( Table 6).…”
Section: Resultssupporting
confidence: 83%
“…In 1998, highest head weight was recorded for sorghum when intercropped with varieties IT90K-277-2 (1791kg/ha) and IT90K-372-1-2 (1750kg/ha) when compared to sole sorghum head weight (1625kg/ha) ( Table 6). This recorded increment in this finding agrees with Wanki et al, 1982 andPal et al, 1993 who had reported yield advantages of legume-cereal intercropping system over sole cropping. However, a significant reduction in head weight was recorded for sorghum when intercropped with varieties IT93K-273-2-1 (1166kg/ha), IT89KD-349 (1250kg/ha) and IT89KD-391 (1375kg/ha).…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…However, Chui and Shibles (1983) attributed the depression in yield of cereal/legume mixtures to shading by cereal of the legume thereby reducing yield. Pal et al (1993) also reported yield reduction in intercropped cereal/legume compared to sole cereal and legume in the Nigerian savanna and that yield reduction due to intercropping depended on the crop component ratios. The highest grain yield of sorghum in the mixture was obtained at 2S:1C planting arrangement but not significantly different from the other planting arrangements.…”
Section: Grain and Stover/haulm Yieldsmentioning
confidence: 99%
“…The significant reduction in yield observed from the intercrop plots may be attributed to inter specific competition among the plants for space, nutrients, light, water etc. Francis et al, (1982), Pal et al, (1993), and Addo-Quaye (2011) all reported reduced intercrop yield in maize / Bean intercrop, Soybean / Maize or Soybean / Sorghum intercrop and Soybean / Maize intercrop respectively, when they investigated the effect of component density on the yield of Sorghum or Maize intercrop with Soybean or Beans.…”
Section: Resultsmentioning
confidence: 99%